Meningkatkan Aktivitas Dan Prestasi Belajar Seni Kriya Dengan Model Pembelajaran Problem Based Learning Pada Siswa Kelas XI IPS 1 SMA Negeri 1 Manggis - I Nyoman Sukadana (Jayapangus Press, 2019)
This study aims to (1) find out how much activity and learning outcomes of students of class XI IPS 1 SMA 1 Manggis can be improved by applying Problem Based Learning Learning Model (2) knowing and describing the responses of students of class XI IPS SMA 1 Manggis to the application of models learning problem based learning. This type of research is classroom action research consisting of two cycles. Each cycle consists of planning, action, observation / evaluation, and reflection. The subjects of this study were students of Class XI IPS 1 in the Senior High School 1 Manggis 2017-2018 Academic Year as many as 30 people. Student activity data was collected through an observation sheet consisting of 6 indicators, each of which included 4 descriptors, data on student learning outcomes were collected through a test in the form of a description, and data on student responses collected through questionnaires. The collected data were analyzed using descriptive analysis. The results showed that the application of the Based Learning Learning Model was able to improve learning activities from the criteria of